Low-Dose Aspirin for PI3K-Altered Localized Colorectal Cancer - Martling, Anna; Myrberg, Ida Hed; Nilbert, Mef; Grönberg, Henrik; Granath, Fredrik; Eklund, Martin; Öresland, Tom; Iversen, Lene H.; Haapamäki, Carola; Janson, Martin; Westberg, Karin; Segelman, Josefin; et al. (New England Journal of Medicine, 2025)
BACKGROUND Aspirin reduces the incidence of colorectal adenoma and colorectal cancer among high-risk persons. Observational studies suggest that aspirin may also improve disease-free survival after diagnosis, particularly among patients with tumors harboring somatic PIK3CA mutations. However, data from randomized trials are lacking. METHODS We conducted a double-blind, randomized, placebo-controlled trial involving patients with stage I, II, or III rectal cancer or stage II or III colon cancer with somatic alterations in PI3K pathway genes. The patients were assigned in a 1:1 ratio to receive 160 mg of aspirin or matched placebo once daily for 3 years. Patients with prespecified PIK3CA hotspot mutations in exon 9 or 20 (group A alterations) and those with other moderate- or high-impact somatic variants in PIK3CA, PIK3R1, or PTEN (group B alterations) were eligible for randomization. The primary end point was colorectal cancer recurrence, assessed in a time-to-event analysis, in patients with group A alterations. Secondary end points included colorectal cancer recurrence in patients with group B alterations, disease-free survival, and safety. RESULTS Alterations in PI3K pathway genes were detected in 1103 of 2980 patients (37.0%) with complete genomic data. Of 515 patients with group A alterations and 588 patients with group B alterations, 314 and 312, respectively, were assigned to receive aspirin or placebo. The estimated 3-year cumulative incidence of recurrence was 7.7% with aspirin and 14.1% with placebo (hazard ratio, 0.49; 95% confidence interval [CI], 0.24 to 0.98; P=0.04) among patients with group A alterations and 7.7% and 16.8%, respectively (hazard ratio, 0.42; 95% CI, 0.21 to 0.83), among those with group B alterations. The estimated 3-year disease-free survival was 88.5% with aspirin and 81.4% with placebo (hazard ratio, 0.61; 95% CI, 0.34 to 1.08) among patients with group A alterations and 89.1% and 78.7%, respectively (hazard ratio, 0.51; 95% CI, 0.29 to 0.88), among those with group B alterations. Severe adverse events occurred in 16.8% of aspirin recipients and 11.6% of placebo recipients. CONCLUSIONS Aspirin led to a significantly lower incidence of colorectal cancer recurrence than placebo among patients with PIK3CA hotspot mutations in exon 9 or 20 and appeared to have a similar benefit among those with other somatic alterations in PI3K pathway genes.
Keywords: Gastroenterology; Gastrointestinal Tract Cancer; Hematology/Oncology; Treatments in Oncology